2014
DOI: 10.1111/jgh.12472
|View full text |Cite
|
Sign up to set email alerts
|

Impact of postoperative hepatitis B virus reactivation in hepatocellular carcinoma patients who formerly had naturally suppressed virus

Abstract: This study shows that naturally suppressed preoperative HBV without application of antiviral agent does not ensure undetectable serum HBV after the surgery, and postoperative viral reactivation might be associated with HCC recurrence.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
23
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(24 citation statements)
references
References 25 publications
1
23
0
Order By: Relevance
“…While several nucleot(s) ide analogues are in wide clinical use, entecavir has higher potency and is associated with lower risk of resistance, potentially making it more effective for many patients . Our use of entecavir in the present study may help explain why our rate of PHR was lower than that in several other studies .…”
Section: Discussionmentioning
confidence: 62%
See 1 more Smart Citation
“…While several nucleot(s) ide analogues are in wide clinical use, entecavir has higher potency and is associated with lower risk of resistance, potentially making it more effective for many patients . Our use of entecavir in the present study may help explain why our rate of PHR was lower than that in several other studies .…”
Section: Discussionmentioning
confidence: 62%
“…In that study, the rate of PHR was significantly lower among those on antiviral therapy (4.7%) than among those not receiving such therapy (20.6%), which is similar to our results. Other studies have consistently shown that antiviral therapy can significantly reduce risk of PHR . A meta‐analysis showed that antiviral therapy with nucleot(s) ide analogues reduces risk of death and of HCC recurrence in patients with HBV‐related HCC following curative treatment, despite a high frequency of lamivudine resistance.…”
Section: Discussionmentioning
confidence: 99%
“…Lee et al . reported that postoperative HBV reactivation was associated with HCC recurrence after surgical resection (including large tumour and multinodularity) in patients with CHB (including both high and low viral loads). Huang et al .…”
Section: Discussionmentioning
confidence: 99%
“…However, there are a few studies investigating whether or not HBV reactivation influences the risk of HCC recurrence after resection. Lee et al [27] reported that postoperative HBV reactivation was associated with HCC recurrence after surgical resection (includ-ing large tumour and multinodularity) in patients with CHB (including both high and low viral loads). Huang et al [25] also showed that HBV reactivation was a risk factor for the recurrence of HCC after surgical resection (including large tumour and multinodularity) in patients with low viral loads (<2000 IU/mL).…”
Section: Discussionmentioning
confidence: 99%
“…Even for patients with low HBV DNA levels, there is still a risk of postoperative reactivation [44,45] . HBV reactivation may worsen liver function, but has also been associated with recurrence of HCC for those with low viral load at baseline [46] .…”
Section: Antiviral Therapy For Hcc Patients Undergoing Surgical Resecmentioning
confidence: 99%